Sessiia Verkhovnogo Soveta Rossiiskoi Federatsii . Sessiia Verkhovnogo Soveta Rossiiskoi Federatsii . Session of the Supreme Soviet of the Russian Federation . Сессия Верховного Совета Российской Федерации - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion on draft laws on land reform and banking activities. Featured in the program: Khasbulatov, Ruslan Imranovich (Chairman of the Supreme Soviet of the Russian Federation) Series description: Broadcast of the sessions of the the Supreme Soviet of the Russian Federation with journalists' comments. Обсуждение законопроектов о земельной реформе и банковской деятельности. В программе участвуют: Хасбулатов, Руслан Имранович (Председатель Верховного Совета Российской Федерации) Описание серии: Трансляция сессий Верховного Совета Российской Федерации с комментариями журналистов.